2014
DOI: 10.1109/tia.2014.2300190
|View full text |Cite
|
Sign up to set email alerts
|

Design of a High-Force-Density Tubular Motor

Abstract: -This paper deals with the design, construction and experimental verification of a high force density, tubular, linear, permanent magnet motor, driven from a high power density matrix converter for an aerospace application. The work also describes the implementation and experimental verification of a novel, thermal management technique for the phase windings of electrical machines. The technique introduces a higher thermal conductivity path between the centre of the slot and the cooling arrangement, thus incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 13 publications
0
31
0
Order By: Relevance
“…Using a Fourier decomposition, it can be shown that the amplitude of the largest harmonic (the 3 rd ), is less than 4% of the amplitude of the fundamental wave. As for a 3-phase, linear synchronous motor [18], the forces of the planar motor can be expressed as shown in (16)(17)(18)(19) …”
Section: B Force Modelmentioning
confidence: 99%
“…Using a Fourier decomposition, it can be shown that the amplitude of the largest harmonic (the 3 rd ), is less than 4% of the amplitude of the fundamental wave. As for a 3-phase, linear synchronous motor [18], the forces of the planar motor can be expressed as shown in (16)(17)(18)(19) …”
Section: B Force Modelmentioning
confidence: 99%
“…An area where this is particularly important, is that of actuation, where electro-mechanical actuators (EMAs) are being increasingly proposed with the aim of substituting the traditional, mechanical and/or hydraulic non-propulsive systems with electrically powered ones, as in [1,2] . In general, an EMA consists of a compact, high speed, electrical machine with gearing or a ball screw to translate rotational into linear motion [3]. With the increasing power density requirements then one of the main challenges being faced today concerns the ability to maintain the required reliability figures.…”
Section: Introductionmentioning
confidence: 99%
“…Considering that stresses will not be constant, any study related to the determination of the lifetime of the insulation will be significantly more complex. As shown in [3,6], in order to ensure the required reliability, it is common practice to design a machine so that the maximum temperature in the slots during the duty cycle is equal to the thermal class temperature of the winding insulation. However, since for EMA applications, the maximum temperature is reached only for a short period, this indicates a potential oversizing of the machine for the specific application.…”
Section: Introductionmentioning
confidence: 99%
“…They are employed in different applications and particularly in variable speed drive systems [1][2][3][4][5][6][7][8][9] where the application demands a more compact and robust solution [10] in place of the traditional two-level, rectifier/voltage source inverter (VSI) circuit [11][12][13]. Matrix converter technology has been considered more recently for aerospace applications [14][15][16][17][18] because of the potential for higher volumetric and gravimetric power density with improved reliability [19] when compared to a back-to-back converter employing large DC-link electrolytic. Two basic types of AC-AC matrix converter structure have been proposed in the literature, the Direct Matrix Converter (DMC) and the Indirect Matrix Converter (IMC) whose circuit schematics are shown in Figures 1a and 1b respectively.…”
Section: Introductionmentioning
confidence: 99%